Preparation of anti rust paint with waste expanded Polystyrene - Muhammad Salihin Zakaria (Universiti Malaysia Perlis, 2009)
A formula for making paint using waste expanded polystyrene foam (EPS) as a binder in place of alkyd resin in most of the commercial paint was developed. Through the experiment the formula follows: the base material (EPS) is 27%, the solvent 43% and the pigment 30%. The morphology and performance characteristic of the prepared polystyrene (PS) based paint were determined and compared with commercial paint. The tests showed that the prepared paint has some advantages such as excellent abrasion resistance, hardness, adhesion, water resistance and alkali resistance. Investigation of solubility test of EPS in solvents indicates that xylene was found to be an effective solvent to make EPS based paint.